Brain‐specific biomarkers in urine as a non‐invasive approach to monitor neuronal and glial damage. (9th December 2022) - Kohlhase, Konstantin; Frank, Franziska; Wilmes, Christian; Koerbel, Kimberly; Schaller‐Paule, Martin A.; Miles, Martha; Betz, Christoph; Steinmetz, Helmuth; Foerch, Christian
Abstract: Background and purpose: This study evaluates the quantitative measurability of glial fibrillary acidic protein (GFAP), neurofilament light chain (NfL), ubiquitin carboxy‐terminal hydrolase L1 (UCH‐L1) and total tau (t‐tau) in urine of patients with acute cerebral damage. Methods: Serum and urine samples were prospectively collected from patients with an acute ischemic stroke or intracerebral hemorrhage (target group) and compared to healthy subjects (control group); samples were measured using ultrasensitive single‐molecule arrays (Simoa®). Glomerular barrier function was assessed based on albumin–creatinine ratio (ACR); biomarker–creatinine ratios were calculated for correction of urine dilution. Results: Ninety‐three urine–serum pairs in the target group and 10 urine–serum pairs in the control group were measured. The mean absolute concentration ± standard deviation in urine of the target and control groups were 184.7 ± 362.4 pg/ml and 27.3 ± 24.1 pg/ml for GFAP ( r = 0.3 [Wilcoxon effect size], p = 0.007), 17.5 ± 38.6 pg/ml and 0.9 ± 0.3 pg/ml for NfL ( r = 0.4, p < 0.005), 320.2 ± 443.3 pg/ml and 109.6 ± 116.8 pg/ml for UCH‐L1 ( r = 0.26, p = 0.014), and 219.5 ± 255.8 pg/ml and 21.1 ± 27.1 pg/ml for t‐tau ( r = 0.37, p < 0.005), respectively, whereas biomarker–creatinine ratio was significantly different only for NfL ( r = 0.29, p = 0.015) and t‐tau ( r = 0.32, p < 0.01). In patients with intact glomerular barrier (ACR < 30 mg/g), only NfL in urine was significantly different between the target and control group and showed a significant correlation with the respective serum concentrations ( r = 0.58 [Pearson's correlation‐coefficient], p < 0.005). Conclusion: All four investigated biomarkers could be measured in urine, with NfL and t‐tau showing the strongest effect size after correction for urine dilution. NfL revealed the most accurate relation between serum and urine concentrations in patients with intact kidney function.